Pengembangan Lembar Kerja Peserta Didik Berbasis POE (Predict, Observe, Explain) pada Materi Kalor Kelas VII SMP - Hilyatul Auliya; Noer ‘Afidah (Mataram University, 2026)
This study aims to develop a Predict–Observe–Explain (POE)-based Student Worksheet (LKPD) on the topic of heat. The study is limited to the subtopic of heat transfer for seventh-grade junior high school students, with the goal of creating a valid and practical tool for use in learning activities. This study employs the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects included subject matter experts, media experts, science teachers, and 29 seventh-grade students at a junior high school in Jombang Regency. Data were collected through observation, interviews, validation questionnaires, and response questionnaires. The research instruments used included validation sheets, lesson implementation sheets, and student response questionnaires. The research results indicate that the POE-based worksheets achieved a validity percentage of 95.5%, classified as highly valid. The practicality results based on the lesson implementation sheets reached 91.3%, classified as highly practical, while the student response questionnaires achieved a percentage of 96.5%, classified as highly practical. The developed worksheets were found to be effective and practical in supporting learning because they helped students understand the concept of heat transfer through systematic predict, observe, and explain activities. Thus, POE-based LKPDs are suitable for use as teaching materials in science classes on the topic of heat transfer for seventh-grade junior high school students.